Research on the Sustainable Development of Modern Wharfs in China—Taking Hong Kong's Blake Pier at Stanley as an Example - Yile Chen; Yurong Ma (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article mainly analyzes the architectural heritage of Blake Pier at Stanley in Hong Kong. Finally, according to the results of field investigation and historical data analysis, some reference suggestions are put forward from the perspective of cultural heritage protection